Deception point - Brown, Dan, 1964- (New York : Pocket Books, 2002)
White House intelligence analyst Rachel Sexton is thrust into a life-or-death situation when she travels to the Arctic to investigate the discovery of a rare meteorite that might prove the existence of extraterrestrial life, and finds instead evidence of scientific trickery.
Adult
Keywords: Americans -- Arctic regions -- Fiction; Conspiracies -- Fiction; Meteors -- Fiction; Presidents -- Election -- Fiction; Scientists -- Fiction; Adventure fiction; Americans -- Arctic regions -- Fiction; Conspiracies -- Fiction; Meteors -- Fiction; Mystery fiction; Political fiction; Presidents -- Election -- Fiction; Scientists -- Fiction; Arctic regions -- Fiction; Arctic regions -- Fiction